Translation memories Swedish Migration Agency - Dahlberg, Simon; Language Council of Sweden, Institute for Language and Folklore (Institute for Language and Folklore, 2020)
Translation memories extracted by Tilde (www.tilde.com) from the data i Texts from the Swedish Migration Agency

Extraction done by Tilde (www.tilde.com) within the framework of ELRC (www.lr-coordination.eu)

Översättningsminnen utvunna av Tilde (www.tilde.com) ur datan i Texter från Migrationsverket

Utvinningen gjord av Tilde (www.tilde.com) inom ramen för ELRC (www.lr-coordination.eu)
Översättningsminnen Migrationsverket
Keywords: immigration policy; invandringspolitik; Emigration and Immigration; Utvandring och invandring; Legislation and legal systems; Lagstiftning och rättssystem; International politics and organisations; Internationell politik och organisationer; Conflict, security and peace; Konflikter, säkerhet och fred; SOCIAL WELFARE POLICY AND SYSTEMS; SOCIAL VÄLFÄRDSPOLITIK OCH VÄLFÄRDSSYSTEM; SOCIETY AND CULTURE; SAMHÄLLE OCH KULTUR; Social Sciences; Samhällsvetenskap; Languages and Literature; Språk och litteratur